Feed factors affecting nutrient excretion by ruminants and the fate of nutrients when applied to soil - Somda, Z.C.; Powell, J.M.; Fernández Rivera, S.; Reed, J.D. (International Livestock Centre for Africa, 1995)
Mixed farming systems in semi-arid West Africa rely on recycling organically bound nutrients to maintain soil productivity. The passage of plant biomass through ruminant livestock plays a major role in the nutrient cycles of this region. The feeding value of crop residues and browses and their impact on nutrient excretion by sheep, and the decompostion of and nutrient mineralisation from crop residues, browse leaves and manure derived from these feeds were studied during the dry, wet and cool seasons in the Sahel of West Africa. The total amount and proportion of nutrients excreted in faeces and urine varied with the lignin:neutral-detergent fibre (NDF), lignin:nitrogen (N) and polyphenol:N ratios of the diets. Feeding browse shifted N excretion from urine to faeces, and from faecal microbial- to undigested feed-N. Initial organic-matter decomposition was more rapid and greater in manure than in browse leaves. Manure decomposition was fastest during the dry and cool seasons. Mineralisation and immobilisation patterns of N and phosphorus (P) in leaves and manure varied considerably. Whereas N and P were released more quickly from manure, browse leaves initially immobilised N and P, particularly during the cool season. Mineralisation of N and P from manure varied seasonally and was highly influenced by the sheep diet. This study showed that the passage of feed through ruminants can be an important regulator of nutrient cycling in this semi-arid region.